Monitoring, Security, and Rescue Techniques in Multiagent Systems - Dunin-Keplicz, Barbara; Jankowski, Andrzej; Szczuka, Marcin (Advances in Intelligent and Soft Computing, 2005)
In today's society the issue of security has become a crucial one. The use of knowledge-based technology in security applications emerges with important applications in monitoring, control, crisis and rescue management. This volume contains extended and improved versions of selected contributions presented at the International Workshop "Monitoring, Security and Rescue Techniques in Multiagent Systems" (MSRAS 2004) held in Plock, Poland, June 7-9, 2004, bringing together world's leading researchers in the field.